Illegal Earning, Motives and Treatments from Islamic Perspective: Analytical Jurisprudential Study - Mohammad, Alkhdhairi Saleh (Journal of Islamic Sciences, 2021)
The research aimed at discuss the issue of illegal earning by highlighting its literal and technical concept; where the researcher clarifies what is meant by illegal earning and the main causes that make people doing it. The types of illegal earning and the position of Islam towards them have been discussed and its negative effects on individual and society in general have been pointed out. The methodologies used were inductive and descriptive methods; the inductive used to find out the provisions of illegal earning as elaborated by jurists, where the descriptive used to explain the texts contained in the subject, as well as the jurists’ opinions and weighting to select the preferable one among them. Several findings have been reached, where the most significant one is that; illegal earning is one of the causes that led to the absence of blessing in many societies. Finally, the study recommends the needs for the researchers to conduct more studies in such important topics that are in need of clarification from the shariah point of view.
Keywords: earning; transactions; property; bribery; interest